1999
DOI: 10.1149/1.1391166
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Fe-Tb Alloys from an Aqueous Electrolyte

Abstract: DC electrodeposition of iron-rich terbium alloys on copper electrodes has been achieved using aqueous citrate solutions. Experiments were carried out in a Hull cell to examine the influence of a wide current density range on the composition and thickness of Fe-Tb alloys. Bright, gray, thin Fe-Tb alloy films were obtained with low current efficiencies. Energy dispersive spectroscopic analysis indicated that Na, S, and O impurities were incorporated in the film. The experimental results demonstrated, for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…At present, these materials are mainly manufactured by pyrometallurgical processes in which separately extracted Fe, Tb and Dy metals are alloyed or compounded by melting processes under inert gas protection [3]. Electro-deposition of Tb-Fe alloy films from aqueous or organic solutions at room temperature was reported [4][5][6], but may be unsuitable for mass production because of the limited solubility of rare earth compounds in the used solutions. It also suffers from low current efficiency and low diffusion coefficient of Tb in Fe at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…At present, these materials are mainly manufactured by pyrometallurgical processes in which separately extracted Fe, Tb and Dy metals are alloyed or compounded by melting processes under inert gas protection [3]. Electro-deposition of Tb-Fe alloy films from aqueous or organic solutions at room temperature was reported [4][5][6], but may be unsuitable for mass production because of the limited solubility of rare earth compounds in the used solutions. It also suffers from low current efficiency and low diffusion coefficient of Tb in Fe at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive research on the integration of small architectures made of complex alloys, fabrication processes compatible with small systems manufacturing have not been fully established. Such is the case with Nd-based permanent magnets [3], giant magnetostrictive Terfenol-D [4], and ferromagnetic shape memory alloys, such as NiMnGa [5]. Bulk fabrication techniques are often employed, which may involve melt spinning, crushing and milling, sintering, ingot synthesis, and processing at high temperatures [3,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Such is the case with Nd-based permanent magnets [3], giant magnetostrictive Terfenol-D [4], and ferromagnetic shape memory alloys, such as NiMnGa [5]. Bulk fabrication techniques are often employed, which may involve melt spinning, crushing and milling, sintering, ingot synthesis, and processing at high temperatures [3,4,6]. Bottom-up methods based on physical vapor deposition techniques have also been employed for multi-alloy fabrication due to their compatibility with micro-and nanosystems processing [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The evolution potentials were found to be substated-and complex agent-dependent. Gong et al 17 reported the electrodeposition of Fe-Tb alloys from aqueous citrate solutions. Thin Fe-Tb films were obtained, but with low current efficiencies.…”
mentioning
confidence: 99%